The Impact of Investment Motivation and Financial Efficacy on Students' Investment Interest in the Capital Market - Yudha Herindra Putra; Muhamad Rival Juliandi; Yoga Pratama; Cahya Adri Priyana (PT Alahyan Publisher Sukabumi, 2025)
The purpose of this study is to analyze and explain in detail the influence of investment motivation, and financial efficacy on students' investment interest in the capital market. The method used in this study is quantitative descriptive with data obtained from the distribution of questionnaires to respondents. The population of this study is 4,000 students of the University of Muhammadiyah Sukabumi City, while the sample was taken using the web raosoft.com sample size calculator with a distribution rate of 50%, an error rate of 10% and a confidence level of 90% so that a sample of 100 people was obtained. The results of this study explain that investment motivation, and financial efficacy on students' interest in investment in the capital market at the University of Muhammadiyah Sukabumi have a positive and significant influence, with an influence of 0.605 or 60.5% while the remaining 39.5% is influenced by other variables outside this study.